1990
DOI: 10.1128/jvi.64.6.2620-2631.1990
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance of specific interactions between herpes simplex virus type 1 ICP4 and sequences from the promoter-regulatory domain of the viral thymidine kinase gene

Abstract: The herpes simplex virus (HSV) type 1 immediate-early regulatory protein ICP4 is required for induced expression of HSV early and late genes, yet the mechanism by which this occurs is not known. We examined the promoter and flanking sequences of the HSV early gene that encodes thymidine kinase for the ability to interact specifically with ICP4 in gel retardation assays. Protein-DNA complexes containing ICP4 were observed with several distinct regions flanking the tk promoter. cis-Acting elements that interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
59
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 57 publications
(96 reference statements)
1
59
0
3
Order By: Relevance
“…ICP4 is a phosphorylated DNA-binding protein with an apparent molecular mass of 175 kDa (6,14,32,46,63). It can bind specifically to DNA, and its binding site is relatively degenerate (14,16,26,28,32,33,(38)(39)(40). ICP4 also appears as three electrophoretic species on sodium dodecyl sulfate (SDS)polyacrylamide gels (46) and as seven species on two-dimensional isoelectrofocusing gels (1).…”
mentioning
confidence: 99%
“…ICP4 is a phosphorylated DNA-binding protein with an apparent molecular mass of 175 kDa (6,14,32,46,63). It can bind specifically to DNA, and its binding site is relatively degenerate (14,16,26,28,32,33,(38)(39)(40). ICP4 also appears as three electrophoretic species on sodium dodecyl sulfate (SDS)polyacrylamide gels (46) and as seven species on two-dimensional isoelectrofocusing gels (1).…”
mentioning
confidence: 99%
“…The expression levels of proteins in cell lines and primary cells or tissues of organisms vary and are differentially controlled due to cell-specific expression of transcription factors and their posttranslational modifications as well as additional factors such as small noncoding RNA [32][33][34][35][36][37][38][39][40]. For cell biological experiments, it has become of interest to achieve precise expression levels for recombinant proteins in cells [41,42].…”
mentioning
confidence: 99%
“…For cell biological experiments, it has become of interest to achieve precise expression levels for recombinant proteins in cells [41,42]. The strength of the well-established herpes simplex virus (HSV) thymidine kinase (TK) promoter has been shown to be in general weaker than that of other widely used viral promoters, the strong CMV and SV40 promoters [33,34,38,42,43]. Studies have shown that the TK promoter contains a TATA box, a CCAAT box, and two SP1 elements ( [32][33][34][35][44][45][46] reviewed in [47]).…”
mentioning
confidence: 99%
See 2 more Smart Citations